2016
DOI: 10.1007/s10342-016-0969-4
|View full text |Cite
|
Sign up to set email alerts
|

Current and future conifer seed production in the Alps: testing weather factors as cues behind masting

Abstract: Temporal patterns of masting in conifer species are intriguing phenomena that have cascading effects on different trophic levels in ecosystems. Many studies suggest that meteorological cues (changes in temperature and precipitation) affect variation in seed-crop size over years. We monitored cone crops of six conifer species in the Italian Alps (1999–2013) and analysed which seasonal weather factors affected annual variation in cone production at forest community level. Larc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 68 publications
3
26
0
2
Order By: Relevance
“…Bisi et al. () showed that spring and summer temperatures and precipitations of one and two years prior to seed maturation influence cone‐crop size in Alpine conifer species. Based on their model and taking into account climate change scenarios, they do not expect marked changes in masting patterns in Alpine forests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bisi et al. () showed that spring and summer temperatures and precipitations of one and two years prior to seed maturation influence cone‐crop size in Alpine conifer species. Based on their model and taking into account climate change scenarios, they do not expect marked changes in masting patterns in Alpine forests.…”
Section: Discussionmentioning
confidence: 99%
“…Bisi et al. () found marked interannual variation in cone production, with years resembling masting events in P. abies , A. alba and L. decidua , whereas P. cembra had less interannual variation in cone‐crop size. All species are wind‐pollinated, and seeds are exclusively dispersed by wind in A. alba , L. decidua and P. abies , whereas in P. cembra, seed dispersal is tightly associated with a bird, the European nutcracker ( Nucifraga caryocatactes ), and establishment is strongly affected by biotic interactions (Neuschulz, Merges, Bollmann, Gugerli, & Böhning‐Gaese, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Favourable climate conditions driven by synoptic weather patterns have been identified as triggers of regionally synchronous pulses of high seed production (e.g., 'mast' years; Koenig and Knops 1998). All seven species in this study exhibit masting dynamics that are hypothesized to be the result of some combination of warm, dry conditions in the growing seasons up to two years prior to cone development (see examples for our study species in Woodward et al 1994, Houle 1999, Sirois 2000, Krebs et al 2012, Bisi et al 2016, Gallego Zamorano et al 2018. However, documentation of seed production in mast years requires long time series and our study design was insufficient to assess controls over mast years.…”
Section: Seed Production Does Not Beget Viable Seed Available For Dismentioning
confidence: 99%
“…We also aim to assess the impacts of climate change and deforestation on trends in red squirrel abundance, while taking into account predator abundance. The summer temperature of the previous year, on the other hand, is one of the most important determinants of the cone crop (Pukkala et al 2010, see also Bisi et al 2016 for the effects of climate on conifer seed production). Due to global warming, when several species shift their area of distribution polewards (Parmesan 2006), we expect to see the more northern populations of red squirrels remain stable or increase as a result of milder winters and increased overwinter survival, which is a critical phase especially for subadults (Selonen et al 2015).…”
Section: Introductionmentioning
confidence: 99%